Tacit and Explicit Knowledge Management at Daima Hotel Padang: A Descriptive Employee Assessment - Hamdi Aziz; Feri Ferdian (Journal of Multidimensional Management, 2026)
This study descriptively assesses employee perceptions of tacit and explicit knowledge management practices at Daima Hotel Padang. A descriptive quantitative survey used a census of all 59 employees and a twelve-item Guttman-scale questionnaire with yes/no responses. Five items addressed tacit knowledge through experience, learning from others, problem solving, and professional practice, while seven items addressed explicit knowledge through standard operating procedures, work systems, and technology use. Tacit-knowledge items generated a 92.9% affirmative-response rate, and explicit-knowledge items generated 92.3%. The overall affirmative-response rate was 92.5%. These percentages represent employee agreement with the questionnaire statements and should not be interpreted as direct measures of the organizational effectiveness of the hotel's knowledge-management system. The weakest tacit item concerned learning from work-related problems (89.8%), while the weakest explicit item concerned the contribution of standard operating procedures to productivity and time efficiency (89.8%). The findings suggest that Daima Hotel Padang has a favorable employee-perception foundation for knowledge sharing and documentation, but management should formalize post-incident learning, mentoring, periodic SOP review, and a centralized digital repository.